Utilization of Byproducts and Waste Materials from Meat and Poultry Processing Industry: A Review - Kulkarni, V. V.; Devatkal, Suresh K. (Journal of Meat Science, 2015)
Livestock sector plays an important role in Indian economy and it is an important sub-sector of Indian Agriculture. The overall growth rate in livestock sector is steady (4-5%) and has been achieved despite very low investment in this sector. As per the report of Department of Animal Husbandry, Dairying and Fisheries, Government of India, the livestock sector alone contributes nearly 25.6% of value of output at current prices of the total value of output in Agriculture, Fishing & Forestry sector. The overall contribution of Livestock Sector in total GDP is nearly 4.11% at current prices during 2012-13 (MOSPI 2014). This contribution would have been much greater had the animal by products been also efficiently utilized. Efficient utilization of by-products has direct impact on the economy and environmental pollution of the country. Non-utilization or underutilization of by-products not only lead to loss of potential revenues but also increases the cost of disposal and may create major aesthetic and health problems. Besides pollution and hazard aspects, in many cases meat and poultry processing wastes have a potential for recycling raw materials or for conversion into useful products of higher value. Traditions, culture and religion are often important when a meat by- product is utilized for food. By-products such as blood, liver, lung, kidney, brains, spleen and tripe have good nutritive value. Waste products from the poultry processing and egg production industry must be efficiently dealt with as the growth of these industries depends largely on waste management. Available information pertaining to the utilization of by-products and waste materials from meat and poultry industry has been reviewed here.
Keywords: By-products; Meat industry; Poultry; Rendering; Utilization; Bioactive compounds